Finite element analysis of the angle range in trans-inferior alveolar nerve implantation at the mandibular second molar - Wenli Wu; Liangyue Song; Jinming Liu; Lingyi Du; Yuhang Zhang; Yingying Chen; Zichun Tang; Ming Shen (BMC, 2023)
Abstract Background Trans- inferior alveolar nerve (IAN) implantation technique was wildly used while the potential appropriate angle range in which the residual alveolar bone can bear the stress without absorption are currently unclear. This study aimed to evaluate the stress distribution pattern of the interface between bone and implant by finite element analysis (FEA) to determine the appropriate range of the implant tilt angle. Methods Cone beam computed tomography (CBCT) images of 120 patients with missing mandibular second molars and vertical bone height < 9 mm in the edentulous area were selected. The distances from the mandibular nerve canal to the buccal cortex, the lingual cortex and the alveolar ridge crest were measured by using a combination of software. The angular ranges of the buccal-lingual inclination of simulated trans-IAN implants were measured and three-dimensional finite element models were constructed in the mandibular second molar area according to the differences of the inclination angles. A vertical load (200N) was then applied to analyze the biomechanical conditions of the implant-bone interface during median occlusion. Results The distance at the second molar from the nerve canal to the buccal cortex, lingual cortex and alveolar crest were 6.861 ± 1.194 mm, 2.843 ± 0.933 mm and 7.944 ± 0.77 mm. Trans-IAN implantation was feasible in 73.33% of patients. The minimum angle and maximum angles of the buccal-lingual inclination of the simulated implant were 19.135 ± 6.721° and 39.282 ± 6.581°. When a vertical static load of 200N was applied, the tensile stress in cortical bone gradually increased with the increase of the implant tilt angle. When the inclination angle reached 30°, the tensile stress (105.9 MPa) exceeded the yield strength (104 MPa) of cortical bone. Compared with the conventional implants, the stress peak value of the vertical ultra-short implant in cortical bone was greater than the stress peak value of the conventional implants at 10°(79.81 MPa) and 20°(82.83 MPa) and was smaller than the stress of the implant at 30°(105.9 MPa) and 40°(107.8 MPa). Therefore, when the bone mass allows, conventional-length implants should be selected whenever possible, and an operative range of the trans-IAN implantation in the mandibular second molar could be retained with an inclination angle of < 30°. Conclusions The mandibular nerve canal at the mandibular second molar was obviously biased to the lingual side, which ensured sufficient bone mass at the buccal side. In most patients with severe mandibular atrophy, it was possible to maintain a safe distance from the nerve canal with conventional-length implants via the trans-IAN implantation technique.